A validated discretized thermal model for application in bare tube evaporative coolers and condensers - du Plessis, Jacques; Owen, Michael (Applied thermal engineering, 2020)
•The paper presents a discretized modelling method for evaporative coolers which is validated against experimental results from a 1.5 m × 1.5 m stainless-steel evaporative cooler with intermediate thermocouples to measure the process fluid temperature profile along the height of the cooler to compare the temperature profile to the results from the model.•This study aims to validate the modelling method which can then be applied to any bare tube evaporative cooler/condenser and specifically to model the bare tube bundle of a hybrid (dry/wet) dephlegmator (with steam as working fluid), used in direct dry cooling for thermal power plants.•The model discretizes the tube bundle into single tube control volumes to numerically integrate the governing differential energy equations for the three working fluids with the 4th-order Runge-Kutta integration procedure.•The discretized modelling method provides insight into the heat transfer rate in individual tubes, which is of great interest for conducting accurate performance modelling of the hybrid (dry/wet) dephlegmator.•The predicted results are within an acceptable accuracy when compared to the measured temperatures, with an average error of 0.62% in the bulk process fluid outlet temperature and a maximum error of 1.45%.•The average error in the intermediate process fluid temperature is 1.87% with a maximum error of 3.4%. A discretized modelling method for evaporative coolers is presented in this paper. This study aims to validate the modelling method which can then be applied to any bare tube evaporative cooler/condenser and specifically to model the bare tube bundle of a hybrid (dry/wet) dephlegmator (HDWD), used in direct dry cooling for thermal power plants. The model discretizes a bare tube bundle into single tube control volumes to numerically integrate the governing differential energy equations for the three working fluids. The discretized modelling method presented here allows for evaluation of the fluid/vapour flow in individual tubes of an evaporative cooler/condenser or HDWD system and therefore offers an additional and valuable level of detail when compared to existing integral models. The model presented here is validated against experimental results from a stainless-steel evaporative cooler with water as process fluid and also compared to experimental results of two other evaporative coolers from literature. The cooler consists of a bare tube bundle (inlet area 1.5 m × 1.5 m) with 20 rows of do = 19.8 mm tubes in a staggered 2.27 × do arrangement. Nine intermediate process fluid temperature measurements are recorded throughout the height of the tube bundle as well as the mean outlet processes water temperature to critically compare the measured and modelled values. Intermediate deluge water temperature is also measured with five thermocouples located in deluge water traps below selected tubes. A total of 16 test points, over a range of air and deluge water flow rates, are analyzed and the average error between the predicted and bulk measured process fluid outlet temperature is 0.62% while the maximum error is 1.45%. The results demonstrate that the intermediate processes water temperatures per tube, the bulk outlet processes water temperature and the deluge water temperature could be accurately predicted with the discretized analytical model. The valuable insight of each tube row indicates the trend of the heat transfer rate throughout the height of the tube bundle where the first tube row from the top, which is the air outlet side, has the highest heat transfer rate where after the heat transfer rate decreases to a minimum, at tube 13 from the bottom, and then increases again in the lower portion of the bundle. The discretized model can be adapted to model the HDWD or other evaporative condensers by employing appropriate steam side heat transfer correlations which will enable the analytical model to predict the rate of heat transfer and associated pressure drops in each tube.